PENGARUH KARAKTERISTIK PEKERJAAN DAN KARAKTERISTIK ORGANISASI TERHADAP KEPUASAN KERJA AUDITOR - Hidayatus Sibyan; Elma Muncar Aditya (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
The objective of this research seemed to examine whether the variable of occupational and arganizational characteristics simultaneously (collectively) and partially (individually) influenced the job satisfaction of auditor at public accountant office in Semarang. The type of this reseach was explanatory research. The population and samples were 117 auditors at 18 public accountant offices in Semarang. The analysis tool used multiple linear regression. The results of simultaneous analysis (F-test) indicated that the variables of accupational characteristic (X1) and organizational characteristic (X2) had significant influence to the job satisfaction of auditor at accountant office in Semarang city with significance rate 0.000. Meanwhile, the partial analysis (t-test) showed that the variable of occupational characteristic (X1) had significant influence to the job satisfaction of auditor with significance rate 0.000, while organizational characteristic (X2) did not have significant influence to the job satisfaction of auditor with significance rate 0.854.